PENGARUH PERBANDINGAN DOSIS KOMBINASI EKSTRAK DAUN MAHKOTA DEWA (Phaleria macrocarpa (Scheff) Boerl) DAN BIJI JINTEN HITAM (Nigella sativa L) TERHADAP ASMA ALERGI DENGAN PARAMETER HITUNG JUMLAH SEL EOSINOFIL PADA MENCIT BALB/C - Suzi Martina Wati; Khamdiyah Indah K; Silma Kaffah (Journal of Innovation Research and Knowledge, 2022)
Asthma is characterized by chronic inflammation of the respiratory tract. Black cumin seeds and leaves of the god's crown are proven to be used as antiasthma. Mahkota dewa is proven to contain alkaloids, saponins and polyvenols that can be used as antiasthma. This study aims to determine the effect of the combination of black cumin seed extract and Mahkota Dewa leaf on allergic asthma in Balb/c mice with the parameter of counting the number of eosinophil cells in the bronchi of Balb/c mice. The test animals used were male Balb/c mice which were divided into 7 treatment groups, namely positive control, negative control, 3 combined doses and 2 single doses. The combined doses given in this treatment were 25/25 mg, 37.5/12.5 mg, and 12.5/37.5 mg. Seven groups were sensitized to ovalbumin in Al (OH)3, day 0 and 14 intraperitoneally. The administration of extracts and Profilas® was carried out from the 1st to the 27th day. OVA aerosol exposure, days 21, 23, 25, 27. On day 28, bronchial tissue was prepared and stained with Haematoxylin Eosin and then observed with a light microscope to count the number of eosinophils. The results obtained were analyzed using the Kruskal-Wallis test. The most effective dose obtained was the combination dose of black cumin seed extract 37.5 mg and Mahkota dewa leaf 12.5 mg/20 g BW.